In vitro rhizogenesis of sugar beet microclones - V. V. Polishchuk; L. M. Karpuk; V. P. Mykolaiko; A. A. Polishchuk; I. I. Mykolaiko (Regulatory Mechanisms in Biosystems, 2017)
The features of rhizogenesis of male-sterile simple hybrids, maternal components of sugar beet heterozosis hybrid and O-types of Darinka variety grown from seeds were investigated. The paper presents the results of studying the main basic nutrient media (B5–A1, B5–A2, B5–A3, B5–A4, B5–A5 and B5–A6) for rhizogenesis, in which the content of macro- and microelements has been reduced by three times, the content of sucrose is reduced by almost 6 times, the amount of agar is reduced by almost five times, while the vitamin РР content is increased by 1.6 times, and the BAP is completely removed. The largest number of rooted microclones was obtained with NAAs by the high indexes of average number of roots and medium indexes of average roots length. To the second, by the number of rooted microclones is assigned, media of 2,4–D, 2,4–DB containing, potassium salt of NAA and IBA were classified, while IAA was characterized by a lower efficiency. The possibilities of regulation of growth and development processes of sugar beet in vitro explants in favor of undifferentiated growth at the stage of proliferation or organogenesis (hemo- and rhizogenesis) have been determined. To improve the quality of rooting of sugar beet plants-regenerants, we have developed the method for dimming agarized nutrient medium with methylene blue at a 0.05% concentration, which made it possible to reduce the inhibitory effect of light on the development of lateral roots. The average index of micro-roots rooting for MS-forms was 81.5 %. The technology of adaptation of micro-roots rooting was developed, in which the plant material at the initial stage of growth had slight morphological changes in the puffer apparatus and stem, but by the end of the vegetation, the plants acquired the appearance characteristic of the donor plants of explants. The clone’s resiliency is reached about 100% in the soil. According to the variability of morphological characteristics in reproduced in vitro sugar beet plants of the MS-forms of the Darynka hybrid, all the plants grown from the regenerants were more, than seed progeny from seed sowing of the same component obtained as a result of the attachment of sterility to the corresponding O-type. It has been found that in vitro cultivation has not weakened, and in some cases even increased the mitotic index of meristem cells of young roots of sugar beet. Most genotypes have reduced the number of pathological mitoses, apparently due to the activation of reparative systems, but did not extend the duration of individual phases of mitosis; without increasing the number of anaphase with bridges and fragments, but changed the number of anaphases with other chromosomal abnormalities. In all variants of the experiment, where activation of growth processes has been observed, the lowest variability of the signs is observed, that is, under the influence of stimulants, which are part of nutrient media, obviously there is unification of cell populations.